2014
DOI: 10.1007/s11606-014-3141-1
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Development Programs for Physicians: A Systematic Review

Abstract: BackgroundPhysician leadership development programs typically aim to strengthen physicians’ leadership competencies and improve organizational performance. We conducted a systematic review of medical literature on physician leadership development programs in order to characterize the setting, educational content, teaching methods, and learning outcomes achieved.MethodsArticles were identified through a search in Ovid MEDLINE from 1950 through November 2013. We included articles that described programs designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
361
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(382 citation statements)
references
References 53 publications
15
361
0
6
Order By: Relevance
“…Feedback and evaluations were valued for improving self-awareness, which, in healthcare leadership programmes, is often missed 8. Systematic feedback, however, does not guarantee behaviour change—it was participants’ focus on learning, which helped them benefit from these practices 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feedback and evaluations were valued for improving self-awareness, which, in healthcare leadership programmes, is often missed 8. Systematic feedback, however, does not guarantee behaviour change—it was participants’ focus on learning, which helped them benefit from these practices 10.…”
Section: Discussionmentioning
confidence: 99%
“…The existing evidence on effective leader and leadership development in and outside of healthcare is not being applied 3 10. The frequent use of brief programmes that focus on conceptual knowledge and individual skills training fail to address personal development and collaborative capacity—both cornerstones for effective leadership 8. The design and delivery commonly employ ineffective teaching approaches, lack relevant theoretical underpinnings and have limited adaptation to the healthcare context 1 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, it is not clear how to best integrate leadership training in residency programs. [8][9][10] In 2012, The Ohio State University Wexner Medical Center Internal Medicine Residency Program implemented the Internal Medicine Leadership Development Program (LDP). The theme for the LDP is ''Leaders From Day One,'' and it starts at the beginning of residents' first postgraduate year (PGY), occurs over the entire year, and targets all residents.…”
Section: Introductionmentioning
confidence: 99%
“…4 The authors searched OVID Medline for English-language peerreviewed studies published between 1950 and 2013. The authors included articles that reported educational programs that trained physicians in leadership skills (or exposed them to leadership concepts), outlined teaching methods, and reported results.…”
mentioning
confidence: 99%